Development of Automatic Real Time Inventory Monitoring System using RFID Technology in Warehouse - Erlangga, Setyawan Bayu; Yunita, Ajeng; Satriana, Sekarjatiningrum Rasmaydiwa (JOIV : International Journal on Informatics Visualization, 2022)
RFID technology is one of the technologies in logistics as an important application in logistics operations and supply chain management. The application of RFID technology can be applied to the inventory control monitoring system in real-time. The inventory monitoring information system can replace the manual system with a computerized system so that the processing of monitoring data is more efficient, effective, and can be controlled directly and accurately. This study presents a case study of a real stock monitoring system based on RFID technology. The design of a real-time stock monitoring system is transitioning from manual to technology by involving computerization in its implementation. This study aims to design an RFID-based real-time stock monitoring system and integrate warehousing systems in the company. The real-time inventory stock monitoring system is still developing, so a simulation is carried out to compare the existing data with the data from the RFID system. We used the existing warehouse layout to try the efficiency of the RFID stock monitoring. Based on the research results, the RFID system increases the efficiency and effectiveness of inventory control. In further research, it is necessary to integrate the inventory optimization model with real-time inventory control with RFID. The integration of real-time monitoring technology can be used as input to the inventory optimization model to be more accurate in providing purchasing policies.